2020
DOI: 10.3390/cells9112395
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CAR and PXR Expression in Health and Disease

Abstract: Pregnane X receptor (PXR, NR1I2) and constitutive androstane receptor (CAR, NR1I3) are members of the nuclear receptor superfamily that mainly act as ligand-activated transcription factors. Their functions have long been associated with the regulation of drug metabolism and disposition, and it is now well established that they are implicated in physiological and pathological conditions. Considerable efforts have been made to understand the regulation of their activity by their cognate ligand; however, addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 305 publications
(392 reference statements)
0
42
0
Order By: Relevance
“…As described above, the CAR, PXR, and PPARa nuclear receptors are highly expressed in liver and are involved in xenobiotic and intermediary metabolism (Omiecinski et al 2011a;Corton et al 2014Corton et al , 2018Yoshinari 2019;Daujat-Chavanieu and Gerbal-Chaloin 2020). Many studies have demonstrated that both CAR and PPARa activators can stimulate RDS in mouse and rat hepatocytes (Lake 2009(Lake , 2018Cohen 2010;Corton et al 2014;Elcombe et al 2014;Corton et al 2018;Yamada 2018).…”
Section: Comparison Of the Hepatic Effects Of Car Pxr And Ppara Activatorsmentioning
confidence: 98%
See 2 more Smart Citations
“…As described above, the CAR, PXR, and PPARa nuclear receptors are highly expressed in liver and are involved in xenobiotic and intermediary metabolism (Omiecinski et al 2011a;Corton et al 2014Corton et al , 2018Yoshinari 2019;Daujat-Chavanieu and Gerbal-Chaloin 2020). Many studies have demonstrated that both CAR and PPARa activators can stimulate RDS in mouse and rat hepatocytes (Lake 2009(Lake , 2018Cohen 2010;Corton et al 2014;Elcombe et al 2014;Corton et al 2018;Yamada 2018).…”
Section: Comparison Of the Hepatic Effects Of Car Pxr And Ppara Activatorsmentioning
confidence: 98%
“…The constitutive androstane receptor (CAR; also known as NR113) is a member of the nuclear receptor superfamily (subfamily 1, group I), which is highly expressed in liver and at much lower levels in small intestine and kidney (The Human Protein Atlashttps://v18.proteinatlas.org/ENSG00000143257-NR1I3/tissue), and is involved in the regulation of xenobiotic metabolism, cell proliferation, apoptosis, energy metabolism, and lipid homeostasis (Omiecinski et al 2011a;Yang and Wang 2014;Yoshinari 2019;Daujat-Chavanieu and Gerbal-Chaloin 2020). CAR can be activated by a large number of chemicals, either by direct ligand binding or by a ligand-independent mechanism resulting in nuclear translocation and heterodimerization with the retinoid X receptor (RXR), which is followed by binding to response elements in DNA (Omiecinski et al 2011a;Yang and Wang 2014;Lynch et al 2019;Negishi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and posttranslational modifications of PXR (phosphorylation, acetylation, SUMOylation, ubiquitination) may potentiate or terminate the activity of PXR. Interestingly, a reciprocal connection between PXR and NFκB pathways has been reported, in which activation of one pathway suppresses the activity, and expression of the target genes for the other (153). Activity of PXR is also regulated via crosstalk with other nuclear receptors (CAR, VDR, HNF4a) or transcription factors (CREB, FOXO, NFkB), like LXR, FXR, or PPARs by sharing or competing for the binding of co-regulatory molecule or response element on the target gene (154-156).…”
Section: Pregnane X Receptor (Pxr)mentioning
confidence: 99%
“…Although amenable to high throughput screening procedures, several pitfalls are frequently encountered but rarely taken into account when resorting to these latter assays. They are the ability of potential ligands to (1) interfere directly with luciferase enzymatic activity; or (2) to activate the nuclear xenobiotic receptors CAR (constitutive androstane receptor) and PXR (pregnane X receptor), which exert pleiotropic effects when activated ( Daujat-Chavanieu and Gerbal-Chaloin, 2020 ).…”
Section: Expected Outcomesmentioning
confidence: 99%